The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s43168-021-00079-6
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of nasal obstruction improves pulmonary functions and oxygenation

Abstract: Background Nasal obstruction is a significant medical problem. This study aimed to examine the effect of nasal obstruction and nasal packing on arterial blood gases and pulmonary function indices, and the impact of the elimination of nasal obstruction on preoperative values. Results The mean age of the study population was 26.6 ± 10.1 years, males represented 50.8%. Spirometric indices showed statistically significant improvement (preoperative forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
0
0
Order By: Relevance
“…This result is consistent with (36), which says that a partial obstruction of the airways due to inflammatory reaction leads to a lack of lung oxygen filling, and thus the process of gas exchange decreases between outside air and lungs (37)(38) (39). Other researchers (40) found that partial obstruction of the nose leads to hypoxia and disturbances in lung function. On the other hand, the correlation was negative and the correlation coefficient value was (-0.103), (-0.058) respectively with no significant difference between the values.…”
Section: Resultssupporting
confidence: 90%
“…This result is consistent with (36), which says that a partial obstruction of the airways due to inflammatory reaction leads to a lack of lung oxygen filling, and thus the process of gas exchange decreases between outside air and lungs (37)(38) (39). Other researchers (40) found that partial obstruction of the nose leads to hypoxia and disturbances in lung function. On the other hand, the correlation was negative and the correlation coefficient value was (-0.103), (-0.058) respectively with no significant difference between the values.…”
Section: Resultssupporting
confidence: 90%
“…It is essential to consider the systemic consequences that can result from the obstruction of the paranasal sinuses. The existing literature has already described how chronic obstructive diseases can disrupt normal blood oxygenation and consequently impact pulmonary blood pressure [14,17,18]. Specifically, Fidan et al demonstrated that even minor nasal obstruction can affect physiological pulmonary ventilation [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature available looking into the effect of blood oxygenation in nasal obstruction patients is a study that showed patients with nasal packing had mild hypoxemia and decreased oxygen saturation. The study showed that elimination of nasal obstruction improved pulmonary functions and oxygenation was significantly improved oneweek postoperative following removal of the nasal pack (Sobh et al, 2021). The intranasal steroid nasal spray (INS) used in this study was mometasone furoate nasal spray (MFNS), which is widely available throughout Malaysia.…”
Section: Introductionmentioning
confidence: 99%